Design-based learning to enhance absorptive capacity for open innovation: the case of 3D Tune-In. Issue 9 (3rd November 2020) - Simeone, Luca; Secundo, Giustina; Messeni Petruzzelli, Antonio; Schiuma, Giovanni
Abstract : Purpose: This paper explores how learning processes supported by intensive use of design can favour absorptive capacity in open innovation contexts characterised by the interaction of a high number of diverse stakeholders. Design/methodology/approach: The paper combines the insights from theory with the empirical evidence gathered by adopting a case study approach. Findings: Findings provide evidence about the role of design-based learning to facilitate intra- and inter-organisational knowledge flows and to sustain absorptive capacity through processes of recognition, internalisation and adoption. Research limitations/implications: The study integrates currently distinct research streams focussing on (1) design research, particularly on how design can support knowledge processes and specific learning processes and (2) open innovation, particularly regarding how to enhance absorptive capacity in those contexts in which a high number of diverse stakeholders interact. Practical implications: This study can help companies, research institutions and other organisations leveraging open innovation to reflect on the potential of design-based learning processes and on how to deliberately facilitate such processes in their projects. Originality/value: The original contribution provided by this study is to explore open innovation through some analytical categories elaborated in design research concerning materially grounded forms of design-based learning. In particular, the study investigates how design supports knowledge transfer, sharing, translation and creation.